Articulação entre as alfabetizações científica, midiática e informacional com a temática imunidade - Graffunder, Karine Gehrke (2021)
The study developed in this dissertation has as its main focus to investigate the relationship between media and information literacy with the scientific one, from the perspective of the context and improvement of Science teaching. The research was developed in two approaches: (1) analysis of the literacies’ historical context and their theoretical foundations; and (2) elaboration of a didactic proposal, articulating the three literacies with the theme of Immunity. In the first approach, we identified the literacies origins and main concepts. For this, we organized and set out information relevant to understanding the relationships between the three types of literacy and Science teaching. In addition, we analyzed the presence of terms of the three literacy types in dissertations and theses that are part of the Brazilian Digital Library of Theses and Dissertations (BDTD). In a simple way, we can conceptualize the literacies through three specific skills: media literacy in 'knowing how to look for reliable sources'; information literacy in ‘knowing how to interpret information’; and scientific literacy in 'knowing how is the elaboration and progress of Science'. In the second approach, we present a notebook with five activities for students in the 7th grade of Middle School. In the teacher's version, the material seeks to lead the student to understand misinformation nuances, exploring the causes and consequences of the contemporary phenomenon of informational overabundance about Immunity. The didactic sequence has the teacher's research objectives; skills to be developed by students; target audience; predicted time; meeting format; and execution procedures. Various procedures/materials are associated to be applied in synchronous and asynchronous moments. Among the activities, a dialogue expository dynamic is contemplated; a bingo game; solving a WebQuest; elaboration of a Pitch; and some games as a review exercise. When asking “what” and “how” Science is taught in Basic Education, it is essential to reflect on the way in which students are reading the contents of Science Nature. The role played by the school in the formal education of subjects is fundamental in this context. Awakening people's interest in daily problems is the first step in combating misinformation. Guiding people to seek information about how Science responds to these problems is the second step, since we cannot prevent misinformation from being produced, but prevent it from spreading. Associating knowledge and skills of scientific literacy with media and information literacy in Science teaching means, therefore, providing the student conditions to understand the process by which scientific knowledge is formulated and validated, since Science also needs to be read and interpreted.